Colorectal Cancer Stem Cells Acquire Chemoresistance Through the Upregulation of F-Box/WD Repeat-Containing Protein 7 and the Consequent Degradation of c-Myc. (31st July 2017) - Izumi, Daisuke; Ishimoto, Takatsugu; Miyake, Keisuke; Eto, Tsugio; Arima, Kota; Kiyozumi, Yuki; Uchihara, Tomoyuki; Kurashige, Junji; Iwatsuki, Masaaki; Baba, Yoshifumi; Sakamoto, Yasuo; Miyamoto, Yuji; et al.
Abstract : The cancer stem cell (CSC) paradigm suggests that tumors are organized hierarchically. Chugai previously established an LGR5 + human colorectal cancer (CRC) stem-cell-enriched cell line (colorectal CSCs) that expresses well-accepted colorectal CSC markers and that can dynamically switch between proliferative and drug-resistant noncycling states. We performed this study to elucidate the molecular mechanisms responsible for evading cell death in colorectal CSCs mediated by anticancer agents. During the cell cycle arrest caused by anticancer agents, we found that c-Myc expression was substantially decreased in colorectal CSCs. The c-Myc expression alterations were mediated by upregulation of F-box/WD repeat-containing protein 7 (FBXW7), as evidenced through FBXW7-small interfering RNA knockdown experiments that resulted in enhanced cell sensitivity to anticancer agents. Upregulation of FBXW7 following drug treatment was not evident in commercially available cancer cell lines. Colorectal CSCs were induced to differentiation by Matrigel and fetal bovine serum. Differentiated CSCs treated with anticancer agents did not show upregulation of FBXW7 and were more sensitive to irinotecan (CPT-11), highlighting the potential CSC-specific nature of our data. The FBXW7 over-expression was further validated in resected liver metastatic sites in CRC patients after chemotherapy. In conclusion, our study revealed that a CSC-specific FBXW7-regulatory mechanism is strongly associated with resistance to chemotherapeutic agents. Inhibition of FBXW7-upregulation in CSCs following chemotherapy may enhance the response to anticancer agents and represents an attractive strategy for the elimination of colorectal CSCs.